“I’m going to change the WIFI password if you don't go outside!”: a qualitative examination of changes in parenting practices over the course of the COVID-19 pandemic - Paterson, Derek; Beauchamp, Mark R.; Masse, Louise C.; Moore, Sarah A.; Faulkner, Guy (Frontiers in Sports and Active Living, 2023)
Introduction Parenting practices are an important influence on the movement behaviours of children. Parenting practices are shaped by various contextual factors (e.g., culture, sociodemographic, community) and are susceptible to external pressures, such as health crises like the COVID-19 pandemic. Situated within the revised Family Ecological Model, the purpose of this study was to qualitatively explore changes in parenting practices over time in relation to the evolving nature of this global event. Methods One-on-one semi-structured interviews with 40 parents of children (aged 7–11) in three Canadian provinces were conducted in August, 2021. A narrative thematic analysis was conducted to develop themes mapping changes in parenting practices and organize the temporal patterns of these changes into shared case trajectories over time. Results Four themes were constructed to highlight changes in parenting practices: (1) Screen time permissiveness, (2) Force and coercion, (3) Agents of unstructured physical activity, and (4) Stepping back from structured physical activity. These themes were organized into three distinct case trajectories that each represent a shared, chronological narrative for how the first 18 months of the pandemic were broadly experienced by parents. The three trajectories were characterized by: (1) Resilience (2) Enduring impact and (3) Adaptive growth. Discussion Parenting practices were changed in response to circumstances in both temporary and enduring manners that may continue beyond the pandemic. Further research is needed to longitudinally assess these trajectories in order to support families and enhance understanding of parenting practices in challenging circumstances.